SDF-1α/OPF/BP Composites Enhance the Migrating and Osteogenic Abilities of Mesenchymal Stem Cells. (15th August 2021) - Li, Linli; Liu, Xifeng; Gaihre, Bipin; Park, Sungjo; Li, Yong; Terzic, Andre; Lu, Lichun
Abstract : In situ cell recruitment is a promising regenerative medicine strategy with the purpose of tissue regeneration without stem cell transplantation. This chemotaxis-based strategy is aimed at ensuring a restorative environment through the release of chemokines that promote site-specific migration of healing cell populations. Stromal cell-derived factor-1 α (SDF-1 α ) is a critical chemokine that can regulate the migration of mesenchymal stem cells (MSCs). Accordingly, here, SDF-1 α -loaded microporous oligo[poly(ethylene glycol) fumarate]/bis[2-(methacryloyloxy)ethyl] phosphate composites (SDF-1 α /OPF/BP) were engineered and probed. SDF-1 α /OPF/BP composites were loaded with escalating SDF-1 α concentrations, namely, 0 ng/ml, 50 ng/ml, 100 ng/ml, and 200 ng/ml, and were cocultured with MSC. Scratching assay, Transwell assay, and three-dimensional migration model were utilized to assess the migration response of MSCs. Immunofluorescence staining of Runx2 and osteopontin (OPN), ELISA assay of osteocalcin (OCN) and alkaline phosphatase (ALP), and Alizarin Red S staining were conducted to assess the osteogenesis of MSCs. All SDF-1 α /OPF/BP composites engendered a release of SDF-1 α (>80%) during the first four days. SDF-1 α released from the composites significantly promoted migration and osteogenic differentiation of MSCs documented by upregulated expression of osteogenic-related proteins, ALP, Runx2, OCN, and OPN. SDF-1 α at 100 ng/ml was optimal for enhanced migration and osteogenic proficiency. Thus, designed SDF-1 α /OPF/BP composites were competent in promoting the homing and osteogenesis of MSCs and thus offer a promising bioactive scaffold candidate for on-demand bone tissue regeneration.